Sustainability in Reconstructive Breast Surgery: An Eco-audit of the Deep Inferior Epigastric Perforator Flap Pathway - Zahra Ahmed, BSc (Hons); Alexander Zargaran, MRCS; David Zargaran, MRCS; Sara Sousi, MRes; Keiron Hakimnia; Sevasti Panagiota Glynou, BSc (Hons); Julie Davies, PhD; Stephen Hamilton, FRCS (Plast); Afshin Mosahebi, FRCS (Plast) (Plastic and Reconstructive Surgery, Global Open)
Background:. The deep inferior epigastric perforator (DIEP) flap provides an effective and popular means for autologous breast reconstruction. However, with the complexity of the pathway, the environmental impact of the pathway has yet to be evaluated. Methods:. A retrospective analysis of 42 unilateral DIEPs at a single reconstructive center was performed. Process mapping and life-cycle analyses were performed for equipment, staff, patients, and land. A bottom-up approach was adopted to calculate carbon dioxide equivalent estimates for the initial consultation, preoperative, intraoperative, and immediate postoperative periods. Results:. This study estimated the carbon footprint of a patient undergoing DIEP flap surgery to be approximately 233.96 kg CO2eq. Induction, maintenance, and running of anesthesia had the highest overall contribution to the carbon footprint (158.17 kg CO2eq, 67.60% overall). Patient and staff travel contributed more than 15% overall carbon emissions in this study. The impact of sterilization was less than half of that from waste management (0.81 versus 1.81 kg CO2eq, respectively). Waste management alone contributed 4.21 kg CO2eq of the overall carbon emissions, the majority of which was accountable to the incineration of 14.75 kg of noninfectious offensive waste. Conclusions:. This study estimates the carbon footprint of the DIEP pathway. Strategies to mitigate the impact of carbon emissions including usage of reusable vs single-use equipment, virtual consultations, standardization of equipment packs, and optimizing waste disposal were suggested areas for improvement. Data from manufacturers on life-cycle assessments were limited, and further work is needed to fully understand and optimize the impact of DIEP surgery on the environment.